DEVELOPMENT OF SCIENCE TEXTBOOK BASED ON SCIENTIFIC LITERACY FOR SECONDARY SCHOOL (Department of Physics, Faculty of Mathematics and Natural Sciences, 2016)
The purpose of this research is to develop scientific literacy-based science text books and to determine the characteristics, validity, readability, as well as the effectiveness of the textbooks.The study started with product development and then continued by feasibility test and readability test. Feasibility test was done with the respondent of lecturer and science teachers of VII, VIII, IX grade at SMP N at Central Java. Readability test used cloze test that filled by VII, VIII, and IX grade students at that schools. The data analysis was done with percentage discription and t-test. The study results in feasibility test showed that the developed literacy science textbook has average score 90,74%. It means the literacy science textbook is suitable. Based on the readability test result, science literacy textbook is easy to learn. The average of score of cloze test was 88,14%. The effectiveness of the developed science textbook was classified as an effective stimulant to increase students’ scientific literacy.Tujuan penelitian ini adalah mengembangkan buku ajar IPA berbasis literasi sains, menentukan karakteristik, kevalidannya, tingkat keterbacaan, dan keefektifannya. Penelitian pengembangan ini dimulai dengan analisis kebutuhan, penyusunan tema, pengembangan buku ajar, uji kevalidan dan keterbacaan buku yang telah dikembangkan. Validasi dilakukan oleh dosen dan guru IPA kelas VII, VII, IX. Uji validitas, tingkat keterbacaan dan keefektifan buku dilakukan di SMP N di Jawa Tengah. Subjek ujicoba adalah siswa kelas VII, VIII, IX. Teknik analisis data menggunakan deskriptif persentase untuk uji kevalidan dan keterbacaan, dan uji t untuk keefektifan. Hasil validasi menunjukkan seluruh buku yang dikembangkan adalah valid dengan rata-rata skor 90,74% berada pada kategori sangat valid. Skor rata-rata tingkat keterbacaan sebesar 88,14% beradapada kategori mudah dipahami. Buku ajar yang dikembangkan efektif untuk meningkatkan kemampuan literasi sains.